The Role of the Consumer Dispute Resolution Agency (BPSK) Regarding Developer Consumer Rights that are Not Fulfilled - Rezky Saftiaan; Indah Harlina; Jum Anggriani (Inovasi Pratama Internasional. Ltd, 2024)
The Consumer Dispute Resolution Agency (BPSK) was established as a solution to avoid resolving consumer disputes through general courts. Proceeding in the general court takes a long time and costs a lot of money, whereas resolving consumer disputes requires fast and cheap procedural law. Consumer Dispute Resolution Agency Provisions in Law Number 8 of 1999 concerning consumer protection which strictly regulates consumer rights that consumers have the right to correct, clear and honest information regarding the actual condition and guarantee of goods/services, of course the Consumer Protection Law accommodating legal certainty for consumers to obtain the rights to everything they want or buy, so that legal certainty for consumers if they do not get clear and correct information from developers or business actors for consumers who buy a house or place to live can be guaranteed if their rights their rights are not fulfilled .